The Efforts Of Islamic Boarding School Darussalam Gontor For Girls Campus 2 To Build Discipline Mental For The Students Class 5 Based On The Behavioristic Theory - Auliya Nur Roufah (Educan : Jurnal Pendidikan Islam, 2018)
Discipline is the most important element and the most effective means in the education process in Islamic Boarding Schools in order to shape the character and mental discipline of the students. In this case, the role of the teacher as a leader in determining strategies, choosing methods, and various approaches to achieve the goals that have been previously planned, namely to form the mental discipline of santri. Islamic Boarding School Darussalam Gontor For Girls Campus 2 gives great attention to the discipline of 5th grade students, because even though they are already big and become administrators of hostel. This study aims to describe and explain 1) the efforts of Islamic Boarding School Darussalam Gontor For Girls Campus 2 in shaping mental class 5 discipline based on behavioristic theory, 2) factors that support and inhibit 5th grade students in obeying discipline. The design used in this study is a descriptive qualitative research design. To achieve these objectives the researcher used 3 methods, namely the observation method, interview method and documentation method. From the analysis data, it has been found that the effort of Islamic Boarding School Darussalam Gontor For Girls Campus 2 in shaping the mental discipline of 5th grade students is provide penalties and rewards, provide advice for 5th grade students who do not deter punishment, habit, modeling, awaken to the importance of discipline for 5th grade students who repeatedly violate discipline, supervision. Factors supporting class 5 students obeying discipline are a. self-awareness, b. mandate, c. become an example for its members, d. punishment.